The impact of physical and virtual environments on human emotions: A pilot study in an adult and community education setting - Bishop, J.; Kommers, Piet (2017)
© 2016 IEEE.This paper concerns an experiment that attempts to understand the impact the physical and virtual environment can have on human emotions. To do this four blended learning workshops are held covering different amounts of technology enhanced learning based on the blended learning continuum. In each workshop there are two of the same participants - one who is autistic and one who is empathic - and then other participants are introduced depending on the aesthetics of the workshop. The study finds that learners deemed 'empathic' require less brain processing for befriending than people deemed 'autistic' do and that those deemed autistic treat every environment the same way and at the same time those deemed 'empathic' focus more on befriending others, regardless of the environment they are in.